The Effect of ASSET Rehabilitation Protocol on the Shoulder Kinematics after Rotator Cuff Tendons Repair - Afshari, Nazanin Fatemeh; Bahrpeyma, Farid; Najafi Ashtiani, Mohammad (Journal of Clinical Physiotherapy Research, 2023)
Introduction: To examine how rehabilitation exercises following rotator cuff surgery using the ASSET protocol affect shoulder kinematics. Material and Methods: This pre-post quasi-experimental study involved 15 individuals aged 40 to 65 who had a degenerative rupture of the supraspinatus tendon. Each participant underwent tendon repair surgery and two stages of rehabilitation. The first stage consisted of passive treatment for six weeks of ASSET protocol, totaling 18 sessions. The second stage included active-assisted and active motions over four weeks, with 12 sessions. Shoulder kinematics, such as scapular upward rotation and glenohumeral elevation, were assessed using a motion analysis system, measuring parameters like range of motion (ROM), peak time, and raising velocity. Kinematic data were collected before and after the ASSET protocol at the sixth and tenth weeks post-surgery. A paired t-test or Wilcoxon signed-rank test was used to compare the kinematic indices before and after the intervention. Results: The results on glenohumeral elevation and shoulder elevation indicated employing ASSET rehabilitation protocol between the sixth and tenth week following rotator cuff tendon repair lead to a significant increase in the ROM in sagittal and scapular planes (P<0.05), but not for ROM on scapula upward rotation (P=0.691). The peak time of scapula upward rotation significantly decreased in both sagittal and scapular planes (P=0.001), while the raising velocity significantly increased in the scapular plane (P=0.009), but not in sagittal plane (P=0.691). There was a significant decrease in peak time and a significant increase in raising velocity in both planes on glenohumeral elevation and shoulder elevation (P<0.05). For the scapulo-humeral rhythm in scapula upward rotation movement, the results showed no significant change in sagittal and scapular planes (P=0.061). Conclusion: The study’s results demonstrate that ASSET protocol can enhance shoulder function following rotator cuff repair surgery by striking a balance between increasing ROM and preserving muscle control.